2017
DOI: 10.1007/s00246-017-1602-0
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoxia Reduces Oxygen Consumption in Children with Pulmonary Hypertension

Abstract: High inspired oxygen concentration (FiO > 0.85) is administered to test pulmonary vascular reactivity in children with pulmonary hypertension (PH). It is difficult to measure oxygen consumption (VO) if the subject is breathing a hyperoxic gas mixture so the assumption is made that baseline VO does not change. We hypothesized that hyperoxia changes VO. We sought to compare the VO measured by a thermodilution catheter in room air and hyperoxia. A retrospective review of the hemodynamic data obtained in children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…We showed that supplemental oxygen therapy lowered mPAP and PVR in PE to an extent similar to previous animal studies on acute, nonobstructive pulmonary hypertension (28,32), or chronic nonautologous PE (29). Similar effects have also been observed in patients with chronic pulmonary hypertension (11,12,30), whereas the effects of oxygen were less pronounced in patients with chronic thromboembolic pulmonary hypertension (13), where the degree of pulmonary vasoconstriction might be limited. Our study provides evidence that supplemental oxygen additionally unloads the RV in the setting of acute PE.…”
Section: Effects Of Oxygen In Pulmonary Embolism and Pulmonary Hypert...supporting
confidence: 86%
See 2 more Smart Citations
“…We showed that supplemental oxygen therapy lowered mPAP and PVR in PE to an extent similar to previous animal studies on acute, nonobstructive pulmonary hypertension (28,32), or chronic nonautologous PE (29). Similar effects have also been observed in patients with chronic pulmonary hypertension (11,12,30), whereas the effects of oxygen were less pronounced in patients with chronic thromboembolic pulmonary hypertension (13), where the degree of pulmonary vasoconstriction might be limited. Our study provides evidence that supplemental oxygen additionally unloads the RV in the setting of acute PE.…”
Section: Effects Of Oxygen In Pulmonary Embolism and Pulmonary Hypert...supporting
confidence: 86%
“…We observed an attenuated effect on HR (and thereby CO), which is in contrast to other animal models investigating oxygen therapy (28, 29). Human studies on pulmonary hypertension have observed reduced HR, although (13, 30). Oxygen may actually cause a minor fall in CO in PE patients (33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The focus is on decreasing oxygen demand and improving oxygen delivery, and supplemental oxygen can be used liberally in this case. There is, in fact, even evidence that in children with pulmonary hypertension, hyperoxia itself reduces oxygen consumption [ 19 ]. Noninvasive ventilatory measures can be considered, including high flow nasal cannula oxygen and continuous positive airway pressure (CPAP), particularly in the patient with lung disease and atelectasis.…”
Section: Discussionmentioning
confidence: 99%
“…Outside of the newborn/neonatal period, oxygen may be used liberally if acceptable for the procedure. Oxygenation will decrease PVR, mildly increase SVR, and may even reduce oxygen consumption and maintain higher mixed venous saturations in the event of right‐to‐left shunt physiology . When the child is breathing spontaneously, the child must be closely monitored for hypoventilation, atelectasis, and hypercapnia, with immediate measures to support ventilation as indicated.…”
Section: Intraoperative Managementmentioning
confidence: 99%